Soil transmitted helminths and schistosoma mansoni infections among school children in zarima town, northwest Ethiopia - Alemu, Abebe; Atnafu, Asmamaw; Addis, Zelalem; Shiferaw, Yitayal; Teklu, Takele; Mathewos, Biniam; Birhan, Wubet; Gebretsadik, Simon; Gelaw, Baye (BMC infectious diseases, 2011)
In Ethiopia, because of low quality drinking water supply and latrine coverage, helminths infections are the second most predominant causes of outpatient morbidity. Indeed, there is a scarcity of information on the prevalence of soil transmitted helminths and Schistosomiasis in Ethiopia, special in study area. Therefore, the aim of this study was to determine the prevalence and associated risk factors of soil transmitted helminths and intestinal Schistosomiasis. Cross-sectional study was conducted among 319 school children of Zarima town from April 1 to May 25, 2009. A pre-tested structured questionnaire was used to collect socio-demographic data and possible risk factors exposure. Early morning stool samples were collected and a Kato Katz semi concentration technique was used to examine and count parasitic load by compound light microscope. Data entry and analysis was done using SPSS-15 version and p-value < 0.05 considered statistically significant. Out of 319 study subjects, 263 (82.4%) of the study participants infected with one or more parasites. From soil transmitted helminths, Ascaris lumbricoides was the predominant isolate (22%) followed by Hookworms (19%) and Trichuris trichiura (2.5%). Schistosoma mansoni was also isolated in 37.9% of the study participants. Hookworm and S. mansoni infections showed statistically significant associations with shoe wearing and swimming habit of school children, respectively. Prevalence of soil transmitted helminths (STH) and S.mansoni was high and the diseases were still major health problem in the study area which alerts public health intervention as soon as possible.